2018
DOI: 10.1093/jhps/hny008
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of deep venous thrombosis following periacetabular and derotational femoral osteotomy: a case for mechanical prophylaxis

Abstract: There are currently no established guidelines for appropriate antithrombotic prophylaxis following periacetabular osteotomy (PAO) or derotational femoral osteotomy (DFO). The purpose of this study was to determine the incidence of clinical deep venous thrombosis (DVT) following PAO and/or DFO wherein a portable, mechanical device and low-dose aspirin were used postoperatively for DVT prophylaxis. Patients who had undergone staged hip arthroscopy and primary PAO and/or DFO were prospectively reviewed. Following… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…In addition, Kraeutler et al . reported that the use of a portable, mechanical compression device and low-dose aspirin effectively lessens the risk of DVT, without increasing the risk of bleeding complications [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Kraeutler et al . reported that the use of a portable, mechanical compression device and low-dose aspirin effectively lessens the risk of DVT, without increasing the risk of bleeding complications [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Have a look at the content once you have accessed the issue and you will see how, perhaps for the first time, there is much more to our content than just hip arthroscopic surgery. There is plenty on venous thromboembolism after hip preservation surgery [ 4 ], be that open or arthroscopic [ 5 ]. I am relieved the authors concluded that the prevalence of venous thromboembolism after hip preservation surgery is, as they describe it, ‘acceptably low’.…”
mentioning
confidence: 99%